Representasi Identitas Budaya Makassar Dalam Pemberitaan Situs Panyingkul.Com Periods 2006-2010 - . Wardah (KOM & REALITAS SOSIAL, 2012)
This research examines the media representation of local cultural identity in an online journalism. The research is based on the assumption that there are some concerns on cultural condition highlighted on Panyingkul, an online media based on Makassar. From this assumption this research tried to analyze news of Panyingkul focusing on culture of Makassar published from 2006 antil 2010. This research intends to understand and comprehend patterns of how local cultural identity is represented on online local media. Using Teun A. Van Dicks discourse, this research concludes that Panyingkul, established amidst the disruption of political and cultural condition in Indonesia, enables to present the real condition of local culture eroded by the influence of modernism. Panyingkul becomes one of citizens media alternatives to which citizen criticize the phenomena of cultural decadency, and of mediums for them to introduce the richness of local tradition and culture in Makassar.